Lessons from the implementation of a trauma center-based program to support primary care providers in managing opioids and pain after trauma hospitalization - Saman Arbabi; Laura-Mae Baldwin; Debra B Gordon; Laura A Katers; Mark D Sullivan; Adrienne James; David J Tauben (Trauma Surgery & Acute Care Open)
Background Decreasing exposure to prescription opioids is critical to lowering risk of opioid misuse, overdose and opioid use disorder. This study reports a secondary analysis of a randomized controlled trial implementing an opioid taper support program directed to primary care providers (PCPs) of patients discharged from a level I trauma center to their homes distant from the center, and shares lessons for trauma centers in supporting these patients.Methods This longitudinal descriptive mixed-methods study uses quantitative/qualitative data from trial intervention arm patients to examine implementation challenges and outcomes: adoption, acceptability, appropriateness, feasibility, fidelity. In the intervention, a physician assistant (PA) contacted patients after discharge to review their discharge instructions and pain management plan, confirm their PCP’s identity and encourage PCP follow-up. The PA reached out to the PCP to review the discharge instructions and offer ongoing opioid taper and pain management support.Results The PA reached 32 of 37 patients randomized to the program. Of these 32, 81% discussed topics not targeted by the intervention (eg, social/financial). The PA identified and reached a PCP’s office for only 51% of patients. Of these, all PCP offices (100% adoption) received one to four consults (mean 1.9) per patient (fidelity). Few consults were with PCPs (22%); most were with medical assistants (56%) or nurses (22%). The PA reported that it was not routinely clear to patients or PCPs who was responsible for post-trauma care and opioid taper, and what the taper instructions were.Conclusions This level I trauma center successfully implemented a telephonic opioid taper support program during COVID-19 but adapted the program to allow nurses and medical assistants to receive it. This study demonstrates a critical need to improve care transition from hospitalization to home for patients discharged after trauma.Level of evidence Level IV.